Bunnicula meets Edgar Allan Crow [compact disc, unabridged] - Howe, James, 1946- (Random House/Listening Library, 2007)
An overly alarmed Chester the cat predicts a gruesome fate for the pets in the Monroe household when a writer of juvenile horror fiction and his bird companion stay overnight.